(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
The present work aims, within a restricted analysis, to study the current stage of democracy in Brazil and its state of recession, demonstrating how often the illegitimate attempt to use the Federal Constitution as a justifying element for autocratic and anti-democratic acts. Some concrete attempts of this use will be addressed, as well as the characteristics of the Constitution and how it represents a limiting and guaranteeing instrument in the face of anti-democratic acts and contrary to fundamental rights